Kontribusi Peran Tenaga Kesehatan terhadap Pencegahan Speech Delay pada Balita : Studi Kasus Puskesmas Baiturrahman Banda Aceh - Ami, Cut Rahmi Muharrina; Yarah, Saufa; Elvandary, Cut Meurah Intan Enn (Jurnal Kesehatan, 2025)
Language development is one of the important aspects of child development. Especially during toddlerhood. Speech and language skills greatly influence social interaction, cognitive development, and children's readiness to enter formal education. However, in recent years, cases of speech delay in toddlers have been increasing, both nationally and locally. Speech delay is characterized by delays in a child's speech compared to their normal developmental stages. The purpose of this study is to explain how health workers at the Baiturrahman Health Center contribute to preventing speech delay in toddlers. The research design is quantitative with a cross sectional approach. The study sample was 94 people with total sampling technique. The independent variable in this study is the role of health workers and the dependent variable is speech delay. This research data was processed with Stata 15 application to see the meaning. The results of the study found that there was a relationship between the role of health workers on the prevention of speech delay in children under five at the Baiturrahman Health Center in Banda Aceh with a p-value of 0.003. Health workers have a significant contribution in preventing speech delay, but further support is needed in the form of training and cross-sector collaboration. Keywords: Delay, Health Center, Toddler, Speech Delay